Improved Cardiovascular Risk among Hispanic Border Participants of the Mi Corazón Mi Comunidad Promotores De Salud Model: The HEART II Cohort Intervention Study 2009–2013 - de Heer, Hendrik Dirk; Balcazar, Hector G.; Wise, Sherrie; Redelfs, Alisha H.; Rosenthal, E. Lee; Duarte, Maria O. (Frontiers in Public Health, 2015)
Background Community resources (parks, recreational facilities) provide opportunities for health promotion, but little is known about how to promote utilization of these resources and their impact on cardiovascular disease risk (CVD). Methods This cohort study evaluated the impact of an intervention called Mi Corazon Mi Comunidad (MiCMiC), which consisted of promoting use of community physical activity and nutrition resources by Promotoras de Salud/Community Health Workers. Participants were assessed at baseline and following the 4-month intervention. Attendance records were objectively collected to assess utilization of intervention programing. Results A total of five consecutive cohorts were recruited between 2009 and 2013. Participants were mostly females (86.0%), on average 46.6 years old, and 81% were low in acculturation. Participants who completed follow-up (n = 413) showed significant improvements in reported health behaviors and body composition. Higher attendance significantly predicted greater improvements. The baseline to 4-month change for the highest vs. the lowest attendance quartiles were for weight (−5.2 vs. +0.01 lbs, p < 0.001), waist circumference (−1.20 vs. −0.56 inches, p = 0.047), hip circumference (−1.13 vs. −0.41 inches, p < 0.001); hours of exercise/week (+3.87 vs. +0.81 hours, p < 0.001), proportion of participants eating five servings of fruits and vegetables/day (+54.7 vs. 14.7%, p < 0.001). Conclusion Following the Promotora-led MiCMiC intervention, substantial improvements in health behaviors and modest improvements in cardiovascular risk factors were found. Greater utilization of community resources was associated with more favorable changes. This study provided preliminary evidence for the effectiveness of Promotora-led interventions for promoting use of existing community resources in CVD risk reduction.